Attitude, Subjective Norm, Perceived Behavioral Controland Intention to Adopt Electric Vehicles in China - Jing , Jin; Yew , Lim Kim; Kowang , Tan Owee; Kiong , Tee Poh; Chen , Yang (International Journal of Accounting and Economics Studies, 2025)
This study utilizes the Theory of Planned Behavior (TPB) framework to examine the elements affecting Chinese consumers’ intention to ‎adopt electric vehicles (EVs). This research systematically applies TPB’s core psychological variables to the EV (electric cars) adoption ‎context in China’s unique market environment. This study aims to examine the relationships between attitude, subjective norm, perceived ‎behavioral control, and intention to adopt EVs among Chinese consumers. It makes a theoretical contribution by validating the applicability of ‎TPB in China’s cultural and market context characterized by collectivism, strong policy orientation, and price sensitivity. From a practical ‎perspective, the investigation furnishes policymakers and marketers with valuable information to promote the advancement of more efficient ‎strategies for EV adoption in the Chinese market. Most existing research on EV adoption has been conducted in Western con‎texts, with limited systematic examination of psychological dimensions in China’s distinct cultural and market environment. While existing ‎studies focus predominantly on economic and technological factors, further development of the psychological dimension and renewable energy ‎research in the Chinese market is needed. The objective of the investigation is to address this disparity by offering empirical evidence of ‎TPB’s effectiveness in predicting Chinese consumers’ intention to adopt EVs.